ANALISIS KEMAMPUAN NUMERIK MAHASISWA JURUSAN AKUNTANSI STIE GENTIARAS - Maria Edistianda Eka Saputri (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
This study aims to determine the effect of numerical ability on Accounting learning outcomes ofSTIE Gentiaras first semester students in 2017/2018 academic year. This research is quantitativeresearch with ex-post facto research method. The population of this study is all first semester studentsof STIE Gentiaras in 2017/2018 academic year, and the sample was selected using simple randomsampling technique. Data collection is done through test and document method.The data analysis technique used in this research is simple regression analysis followed by testof determination and T test. Based on the result of the research, it can be concluded that: (a)Regression equation X (Numeric Ability) to Y (Accounting Learning Outcomes) is Y = 35,374 + 0,408X1; (b) numerical ability has significant effect on Accounting learning result of the first semester studentof STIE Gentiaras in 2017/2018 academic year; (c) The effect of variable X (Numerical Ability) tovariable Y (Accounting Learning Outcomes) is 36.6%